Unveiling the CO2 adsorption capabilities of carbon nanostructures from biomass waste: An extensive review - Arun Kumar Senthilkumar; Mohanraj Kumar; Mohammed Abdul Kader; Mohd. Shkir; Jih-Hsing Chang (Carbon Capture Science & Technology)
Investigating alternate feedstocks is necessary because of the increasing need for sustainable materials and technologies. Though there are many advanced technologies for sequestering CO2 from the atmospheric air. The most favourable route is using activated carbon derived from biomass. Biomass, a renewable material readily available at abundant levels, is one of the intriguing options for creating carbon nanostructures. In this review, various biomass sources like wood, plants, and aquatics are discussed for the production of materials with nanostructured carbon. Owing to their distinct characteristics, including their large surface area, pore size, and ability to attach various functional groups, they are the perfect source material for CO2 adsorption. Additionally, tailoring the surface chemistry of nanostructured materials offers different kinds of adsorption mechanisms for CO2 capture, which are covered in detail. Furthermore, this article offers a thorough review of carbon nanotube (CNT), graphene, and other diverse carbon structures obtained from different biomass sources, and also their potential future study areas are discussed. Even yet, there are still problems with optimizing desorption efficiency and raising yield levels. By concentrating on these areas of research, it will be possible to fully realize the potential of carbon nanostructures obtained from biomass. Additionally, the increasingly growing global commitment to ‘net zero’ with a high level of investments in clean solutions will open the door for more sustainable futures with cutting-edge material technologies and effective CO2 adsorption.